The (Un)Conscious Pariah: Canine and Gender Outcasts of the British Raj - Hamzić, Vanja (2013)
In the post-1857 colonial era, the Indian social and legal landscape underwent a seismic shift, caused by an evermore direct and forceful British rule in many spheres of life, including human-animal and gender relations. This paper provides a brief analysis of this shift through the prism of colonial control of both human and canine pariahs in the Raj, which was fraught with conflicts, debates and moral crises. Since early colonial times, the word 'pariah' in the English language has come to denote any person or animal that is generally despised or avoided. It is derived from the paraiyar (sing. paraiyan), a low-caste group found in the southernmost part of the Indian subcontinent, which probably owes its name to the Tamil word for a drum (parai). For British colonial masters, however, the word 'pariah' was applicable to the whole of the Indian lowest castes, human outcasts in general, and, curiously perhaps, to India’s street dogs. Both dogs and humans of the colony deemed astray of Victorian propriety were subject to the changing tides of colonial rule. Abhorred and pitied at the same time, these outcasts were the basis for much of the prevalent civilisatory discourse, which lamented the cruelty of the native in dealing with such ‘aberrations’ while ultimately seeking to do away with them altogether. In 1869, the first Act for the Prevention of Cruelty to Animals for Bengal was passed, which was later extended to all of India. Two years later, the notorious Criminal Tribes Act was enacted, which included, in Part II, the category of ‘eunuch’. With the help of Hannah Arendt’s concept of ‘the conscious pariah’, this paper revisits these two significant pieces of colonial legislation and their effects on the lifeworlds of the human gender-variant and the canine pariah of India.